2017
DOI: 10.1073/pnas.1702155114
|View full text |Cite
|
Sign up to set email alerts
|

Empathy and well-being correlate with centrality in different social networks

Abstract: Individuals benefit from occupying central roles in social networks, but little is known about the psychological traits that predict centrality. Across four college freshman dorms (n = 193), we characterized individuals with a battery of personality questionnaires and also asked them to nominate dorm members with whom they had different types of relationships. This revealed several social networks within dorm communities with differing characteristics. In particular, additional data showed that networks varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 40 publications
(32 reference statements)
3
85
0
Order By: Relevance
“…Participants. As part of a larger study on social networks (12), newly matriculated college students were recruited from two freshman-only dormitories at Stanford University. Ninety-seven freshmen for the larger study and 52 students who were eligible and willing to participate in the fMRI scanning session provided informed consent.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants. As part of a larger study on social networks (12), newly matriculated college students were recruited from two freshman-only dormitories at Stanford University. Ninety-seven freshmen for the larger study and 52 students who were eligible and willing to participate in the fMRI scanning session provided informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Socially valuable others provide high-quality support and minimize others' stress (7)(8)(9)(10). They also tend to be connected to other community members, and close relationships with them can offer a gateway to additional social resources (11,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These models focus on a handful of key parameters, which can be grouped as: (1) degree centrality, (2) eigenvector centrality, (3) diffusion centrality, and (4) bridging (Jackson, 2019). While one might not wish to be central in an HIV infection network, centrality is viewed as an advantage in most social networks and is correlated with financial success (Burt & Ronchi, 2007) and wellbeing (Morelli, Ong, Makati, Jackson, & Zaki, 2017). Degree centrality captures "popularity," the sheer number of connections an individual might have, capturing the speed at which these individuals can easily transmit information to a wide group at once.…”
Section: Example #2: Revisiting Influence and Information Transmissionmentioning
confidence: 99%
“…Network analysis has therefore allowed researchers to apply new tools while revisiting old questions about social influence. For example, researchers have investigated whom individuals gravitate to in a network, finding that empathetic people are chosen for situations which require trust and support, while positive people are chosen for situations that are fun and exciting (Morelli et al, 2017). Other work has found that people give less money to those who are more socially distant (unknown) friends of friends in standard economic games (Candelo, Eckel, & Johnson, 2018;Goeree, McConnell, Mitchell, Tromp, & Yariv, 2010).…”
Section: Example #2: Revisiting Influence and Information Transmissionmentioning
confidence: 99%